2006
DOI: 10.1111/j.1600-0420.2005.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular oxygen saturation in retinal vessels in normal subjects and open‐angle glaucoma subjects

Abstract: ABSTRACT.Purpose: To measure the oxygen saturation (SO 2 ) in retinal arterioles and venules in patients with glaucomatous optic neuropathy. Methods: We examined SO 2 in retinal arterioles and venules simultaneously by imaging spectrometry. Oxygen saturation was evaluated according to the difference of the extinction spectra of haemoglobin and oxyhaemoglobin. The arteriovenous difference (avD) was calculated by (SO 2art -SO 2ven ). The optic nerve head topography was estimated by Heidelberg retinal tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 38 publications
6
59
3
Order By: Relevance
“…17 In this study, no significant differences were observed in the oxygen saturation of the retinal venules between normal and glaucomatous eyes (normal-tension glaucoma and POAG). Arteriolar oxygen saturation was significantly lower in the normal-tension glaucoma cohort compared with normal subjects but not in the POAG cohort.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…17 In this study, no significant differences were observed in the oxygen saturation of the retinal venules between normal and glaucomatous eyes (normal-tension glaucoma and POAG). Arteriolar oxygen saturation was significantly lower in the normal-tension glaucoma cohort compared with normal subjects but not in the POAG cohort.…”
Section: Discussioncontrasting
confidence: 50%
“…Studies using various retinal oximetry devices to measure the oxygen saturation of the retinal vasculature in glaucoma have been reported. [12][13][14][15][16][17][18][19][20] Hyperspectral imaging combines spectroscopy with digital imaging whereby spectral data (using numerous contiguous wavelengths of light) are obtained in every pixel of an image plane. An oximetry study of the retinal vascular network using a hyperspectral imaging system (images acquired using more than three contiguous wavelengths) in glaucoma has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Disparities in oxygen utilization between the left and right eyes, such as those that occur in diabetic retinopathy, could be measured to screen for retinal disease as well as for monitoring responses to interventions and experimental treatments. 6,7 Retinal venous oxygen saturation has been demonstrated to predictably decrease during hemorrhagic shock, to rise with resuscitation, and to correlate with central venous oxygen saturation. 2,3,8,9 Early goal-directed therapy (EGDT) for patients with severe sepsis-a resuscitation algorithm using physiologic end points, including central venous oxygen saturationhas been shown to increase the survival of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…The future of understanding the ischemic aspect in the development of glaucoma may be by optical measurement of retinal vessel oxygenation. Oxygenation of retinal arteries was found to be lower in normal-tension glaucoma patients than in healthy subjects (Michelson et al, 2006). Other factors influence the perfusion of the optic nerve and participate in the development and progression of the disease.…”
Section: Pathogenic Theoriesmentioning
confidence: 99%